Pool boiling of R-134a and R-123 on smooth and enhanced tubes - Gorgy, Evraam I. (Kansas State University, 2008)
This project studied the pool boiling of R-134a and R-123 on smooth and enhanced tubes. This is the 1st phase of ASHRAE project RP-1316 "Experimental Evaluation of The Heat Transfer Impacts of Tube Pitch in a Highly Enhanced Surface Tube Bundle". A Turbo BII-HP and a Turbo BII-LP enhanced tubes were used in this study. These tubes were manufactured and donated by Wolverine Tube, Inc. Four different boiling cases were tested, R-134a on smooth tube, R-123 on smooth tube, R-134a on Turbo BII-HP tube, and R-123 on Turbo BII-LP tube. The first step in this study was performing a modified Wilson plot analysis, once completed, the average and local refrigerant heat transfer coefficients were determined. This thesis also presents the enthalpy-based heat transfer analysis (EBHT), a new method for determining the heat exchanger's overall heat transfer coefficient as a function of the enthalpy change of incompressible fluids. The test tubes' outer diameter is 19.05 mm and length is 1 m. Tests were conducted in a single tube test section, in which the test tube was water heated. All tests were conducted at a saturation temperature of 4.44 °C. The heat flux range is 9.2-126.6 kW/m[superscript]2 for testing with R-134a on smooth tube, 9.2-58 kW/m[superscript]2 for R-123 on smooth tube, 4.1-135.1 kW/m[superscript]2 for R-134a on Turbo BII-HP tube and 4.7-59.8 kW/m[superscript]2 for R-123 on Turbo BII-LP tube. Results show that the heat transfer coefficient increases with heat flux for all cases except the case of R-134a on Turbo BII-HP tube, where it experiences a trend change. Part of this study was comparing the smooth and enhanced tubes performances. R-134a Turbo BII-HP tube to smooth tube heat transfer coefficient ratio changes from 4 at low heat flux to 1.7 at high heat flux. R-123 Turbo BII-LP tube to smooth tube heat transfer coefficient ratio changes from 24 at low heat flux to 7 at high heat flux. The performance of Turbo BII-HP and Turbo BII-LP was found to be very similar over the tested heat flux range of the Turbo BII-LP tube. Comparison plots with available literature are presented.
Keywords: Pool Boiling; Refrigerants; EBHT; Enthalpy-Based Heat Transfer Analysis; Engineering, Mechanical (0548)